Knowledge Representation for Potential Field of Study Recognition - Mappe, Santy; Wongthongtham, Pornpit (IEEE, 2013)
Knowledge Representation is a part of Artificial Intelligence that focuses on the formalism design. The knowledge about a specific domain is expressed epistemologically and computationally. One of the main reasons for this is that knowledge must be represented so as to easily identify the structure and characteristics of classes and the relationship among them. This paper will focus on the systematic investigation of ontology's formula that is presented by Description logics. We believe that Description logics be able to sketch, define, integrate and maintain the ontology.